Language and Autonomy in Neal Stephenson's Snow Crash. - Embry, Jason (MOSF Journal of Science Fiction)
Neal Stephenson’s Snow Crash captures the joy and excitement of many new developments of the technologized world: anonymity within virtual worlds, rapid production, instant consumer satisfaction, and the accessibility of massive amounts of information. The novel tells the story of hackers who subvert the mind control schemes of an evangelical media mogul through their skills with writing computer code and their belief that free will is still essential to humanity. The battle for control in literature is nothing new, but this version pits Gnostic exploration of self-deification against Lacan’s Big Other. The synthesis of these mystical and psychological approaches makes this struggle unique. In Snow Crash, virtual reality and the Lacan’s Symbolic order come crashing together so that in order to save those in the real world, the protagonists must actually stop the spread of information and defeat a virus in the virtual world. Stephenson ends the novel with two figures whose code changes reality, one virtual and one physical—Hiro and Juanita. While Hiro can design and manipulate the Metaverse, Juanita possesses the power to reprogram people in reality. Like hackers, their skill and knowledge enable them to act as watchdogs for any other threat posed to free will. If a person can possess this ability in the past, then they should be on guard to manage the information collected in the present to resist the influence on free will in the future.